A Nine-Year Audit of Open-Access Upper Gastrointestinal Endoscopic Procedures: Results and Experience of a Single Centre. (2011) - Keren, Dean; Rainis, Tova; Stermer, Edy; Lavy, Alexandra
Abstract : BACKGROUND: The appropriateness and safety of open-access endoscopy are very important issues as its use continues to increase. OBJECTIVE: To present a review of a nine-year experience with open-access upper gastrointestinal endoscopy with respect to indications, diagnostic efficacy, safety and diseases diagnosed. METHODS: A retrospective, observational case series of all patients who underwent open-access endoscopy between January 2000 and December 2008 was conducted. Indications were classified as appropriate or not appropriate according to American Society of Gastrointestinal Endoscopy (ASGE) guidelines. Endoscopic diagnoses were based on widely accepted criteria. Major complication rates were assessed. RESULTS: A total of 20, 620 patients with a mean age of 58 years were assessed, of whom 11, 589 (56.2%) were women and 9031 (43.8%) were men. Adherence to ASGE indications led to statistically significant, clinically relevant findings. The most common indications in patients older than age 45 years of age were dyspepsia (28.5%) and anemia (19.7%) in the ASGE-appropriate group, and dyspepsia in patients younger than 45 years of age without therapy trial (6.6%) in the nonappropriate group. Of the examinations, 38.57% were normal. Hiatal hernia and nonerosive gastritis were the most common findings. Important diagnoses such as malignancies and duodenal ulcers would have been missed if endoscopies were performed only according to appropriateness. There were only two major complications and no mortalities. CONCLUSIONS: Open-access upper gastrointestinal endoscopy is a safe and effective system. More relevant findings were found when adhering to the ASGE guidelines. However, using these guidelines as the sole determining factor in whether to perform an endoscopy is not advisable because many clinically relevant diagnoses may be overlooked.